Miracle healing and exorcism in South Indian Pentecostalism - Bergunder, Michael (Global pentecostal and charismatic healing, 2011)
This chapter argues that missionary success of the South Indian pentecostal movement in church planting is largely attributable to claims of miracle healing and exorcism, practices that exhibit phenomenological parallels to popular Hinduism and reflect the contextualization of Christianity. Belief in evil spirits is widespread among Christians, and pentecostals borrow demonology and etiologies of disease and misfortune from folk religiosity. Pentecostal pastors and evangelists, many of whom are ethnically Tamil, compete with Hindu Mantiravātis, or exorcists, and gurus believed to be avatāras, or divine incarnations. Key leaders include D. G. S. Dhinakaran (1935-2008). Unspectacular healing prayer occurs daily apart from big evangelistic rallies, and church growth also occurs through lay outreach to family, neighbors, and coworkers, and by pastoral care and institution-building. Modern medicine is not rejected as contrary to “faith” (except by the Ceylon Pentecostal Mission), but neither is it widely available or viewed as unquestionably authoritative.